COMPARATIVE ANALYSIS OF THE NOVELS "COFFIN" BY NAZAR ESHANKUL AND "THE PLAGUE" BY ALBERT CAMIUS (Scientific journal of the Fergana State University, 2025)
This article contains a number of information analyses regarding the updates of the artistic plot, composition and style that have entered the Uzbek narrative today. Thanks to independence, under the influence of changes in human thinking, era and society in our national literature today it has become possible to translate, understand and correctly interpret the works of Camus. Writers such as N. Eshonkul are influenced by the traditions of Western modernist literature, their works describe and reveal not events, but the person himself, his thoughts, pain, suffering, psyche, psychological worldview. The stories of N. Eshonkul "The Coffin" are compared with the plot and characters of the works of Albert Camus, the general and various aspects characteristic of the artistic expression of the theme and conceptual ideas presented in the works are assessed.